The impact of extreme weather events on fertility preference and gender preference in Bangladesh - Atiqul Haq, Shah Md (Frontiers in Environmental Science, 2023)
The link between population dynamics and climate-related severe events is complicated. Extreme weather events (EWEs), along with other factors such as socioeconomic and cultural factors, influence population dynamics, particularly changes in fertility, mortality, and migration. This study focuses solely on the fertility aspect of climate change and aims to investigate it in Bangladesh, which is extremely sensitive to climate change and EWEs such as floods, cyclones, and droughts. On a regular basis, the country is confronted with a number of EWEs. The current study examines how different types of extreme weather events affect vulnerable people's decisions to have children or to prefer children of a certain gender. People who reside in a particular area may be more vulnerable to particular EWE types, which may result in different preferences for fertility and gender. This study employed individual-level data from three places (flood-prone, drought-prone, and cyclone-prone), each exposed to a distinct hazard, to address this issue, and collected pertinent information from 177 respondents in the susceptible areas using a survey questionnaire. The quantitative results show that the gender of the first child, the perceived risk of infant death due to EWE, the opinion on having more children to recover from the damage and losses caused by EWE, government and non-governmental organization (NGO) support during EWE, and the intended timing of child bearing (after or before EWE) are all significant factors influencing fertility preferences and gender preferences. The findings also indicate that the three regions under investigation have statistically distinct preferences for fertility and gender. There were larger differences between flood-prone areas and drought- and cyclone-prone areas. The complex issue of variations due to different EWEs requires more in-depth studies with larger samples and different methodological techniques.